Fostering Actions of Competence Broadening Higher Order Thinking Skills as a Basis for Standardized Test-Taking - Esperanza Martínez Rojas (Asociación Colombiana de Profesores de Ingles, 2007)
This article reports on a research project that aimed at selecting actions of competence and how these can be fostered to broaden higher order thinking skills as a basis to achieve a high performance in standardized test taking by the senior students of a private high school in Bogotá. The research was done under action research following the model of Cohen & Manion (1980), in which a sequence of steps was carried out to identify the problem at hand that concerns the pedagogical labor of arriving at conclusions that lead into pedagogical implications and thoughts on future continuation with the topic.